Strength and Durability of Sustainable Self-Consolidating Concrete with High Levels of Supplementary Cementitious Materials - Salih, Moslih Amer; Ahmed, Shamil Kamil; Alsafi, Shaymaa; Abullah, Mohd Mustafa Al Bakri; Putra Jaya, Ramadhansyah; Shayfull Zamree, Abd Rahim; Aziz, Ikmal Hakem; Thanaya, Nyoman Arya (MDPI AG, Basel, Switzerland, 2022)
Self-consolidating concrete (SCC) has been used extensively in the construction industry because of its advanced characteristics of a highly flowable mixture and the ability to be consolidated under its own weight. One of the main challenges is the high content of OPC used in the production process. This research focuses on developing sustainable, high-strength self-consolidating concrete (SCC) by incorporating high levels of supplementary cementitious materials. The overarching purpose of this study is to replace OPC partially by up to 71% by using fly ash, GGBS, and microsilica to produce high-strength and durable SCC. Two groups of mixtures were designed to replace OPC. The first group contained 14%, 23.4%, and 32.77% fly ash and 6.4% microsilica. The second group contained 32.77%, 46.81%, and 65.5% GGBS and 6.4% microsilica. The fresh properties were investigated using the slump, V-funnel, L-box, and J-ring tests. The hardened properties were assessed using a compressive strength test, while water permeability, water absorption, and rapid chloride penetration tests were used to evaluate the durability. The innovation of this experimental work was introducing SCC with an unconventional mixture that can achieve highly durable and high-strength concrete. The results showed the feasibility of SCC by incorporating high volumes of fly ash and GGBS without compromising compressive strength and durability.